Case Report of Cylindrical Grip on Improving Upper Limb Muscle Strength of SNH Patient - Azizah, Rizkia Nurul; Anam, Akhyarul (Indonesian Journal of Global Health Research, 2024)
Non-hemorrhagic stroke patients who do not get optimal treatment will experience disability or physical weakness such as paralysis and weakened muscle strength, which results in a lack of joint range of motion, limb function, and decreased daily life activities. One of the ROM techniques to help recover the upper extremities to stimulate the hands, can be done with cylindrical grip exercises which are functional hand exercises by grasping a cylindrical object in the palm of the hand which aims to support the recovery of the ability to move and function of the hand. Objective: This case repost aims to determine the effect of giving cylindrical grip to stroke ptients to increase muscle strengt in the upper extremities. Method: The method used is a descriptive case report design based on Evidance Based Nursing (EBN) conducted on two subjects with non-hemorrhagic stroke. Results: After the implementation of ROM exercise nursing: cylindrical grip for 3 days in each patient starting from 18-22 September 2023 which was carried out for 5 minutes and repeated 7 times, changes were obtained in the muscle strength of Mrs.M's right hand which was originally 3 to 4 and Mr.W which was originally left hand muscle strength 2 to 4. Conclusions: ROM Exercise: Cylindrical grip can improve upper extremity muscle strength in non-hemorrhagic stroke patients.